Empirical model of human blood transverse relaxation at 3 T improves MRI T2 oximetry - Bush, Adam; Borzage, Matthew; Detterich, John; Kato, Roberta M.; Meiselman, Herbert J.; Coates, Thomas; Wood, John C. (Magnetic resonance in medicine, 2017)
Purpose We sought a human blood T2‐oximetery calibration curve over the wide range of hematocrits commonly found in anemic patients applicable with T2 relaxation under spin tagging (TRUST). Methods Blood was drawn from five healthy control subjects. Ninety‐three in vitro blood transverse relaxation (T2b) measurements were performed at 37°C over a broad range of hematocrits (10–55%) and oxygen saturations (14–100%) at 3 Tesla (T). In vivo TRUST was performed on 35 healthy African American control subjects and 11 patients with chronic anemia syndromes. Results 1/T2 rose linearly with hematocrit (r2 = 0.96), for fully saturated blood. Upon desaturation, 1/T2 rose linearly with the square of the oxygen extraction, (1‐Y)2, and the slope was linearly proportional to hematocrit (r2 = 0.88). The resulting bilinear model between 1/T2, (1‐Y)2, and hematocrit had a combined r2 of 0.96 and a coefficient of variation of 6.1%. Using the in vivo data, the bilinear model had significantly lower bias and variability than existing calibrations, particularly for low hematocrits. In vivo Bland Altman analysis demonstrated clinically relevant bias that was −6% (absolute saturation) for hematocrits near 30% and rose to + 6% for hematocrits near 45%. Conclusion This work introduces a robust bilinear calibration model that should be used for MRI oximetry. Magn Reson Med 77:2364–2371, 2017. © 2016 International Society for Magnetic Resonance in Medicine